Evaluación del factor de riesgo ruido laboral y su incidencia en los trabajadores del área banco de pruebas técnicas de la empresa Galardiesel. Diseño de un manual de prevención - Galarza Caiza, Rómulo Francisco (2017)
The presentinvestigation work is addressed to evaluate noise levels prevalent at CompanyService Galardiesel Cia. Ltda. In the area of technical test banks, to determine if the noise levels are high and affects the health of the workers, in order to propose a noise prevention manual. For the development of this project the noise survey is applied to the workers of the area of technical test banks determining that the noise level is high in the work area. Based on these results, we analyze the risk factors using the risk matrix of the INSHT, which considers the probability and consequence, which allowed the accurate information to be determined by determining the presence of the physical noise risk within the test bed area with the level of MODERATE estimation. In order to deepen this research, a study of the sound pressure levels in each work place of the area of test benches are carried out. The study uses as reference the methodologies of recognized international organizations, such as ISO 9612: 2009. The result of the evaluations establishes that the noise levels within the assembly bank area is between at least 85.3 dBA while at the universal test bench 93.4 dBA at most these values are above the permissible maximum (85 dBA) by the Ecuadorian norm. The hypothesis that is proved is that at these levels in which the tasks are carried out in the different jobs, if immediate preventive actions are not taken, they will result in health effects, as well as occupational diseases to the workers of the area of banks of tests. The study of occupational noise determined the presence of this factor in an INTOLERABLE risk level for the workers, so based on these results a manual of prevention was elaborated in which preventive measures are determined to reduce the physical noise risk.